The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/0886022x.2019.1598432
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy activity and expression pattern of autophagy-related markers in the podocytes of patients with lupus nephritis: association with pathological classification

Abstract: Objective: To identify the significance of autophagy in lupus nephritis (LN). Methods: The number of autophagosomes in podocytes was counted and the expression of multiple molecular markers associated with autophagy was evaluated in LN specimens: in renal biopsy specimens from 90 patients with LN and 15 healthy controls, autophagosomes in podocytes were counted using transmission electron microscopy and the expression levels of four autophage related proteins including Beclin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…Autophagy is a highly conserved intracellular catabolic process for degradation of proteins and organelles via the lysosomal pathway (Mizushima and Komatsu, 2011;Mizushima et al, 2008). As terminally differentiated cells, podocytes exhibit a high level of basal autophagy, which play a pivotal role for maintaining podocyte's homeostasis (Hartleben et al, 2010;Yasuda-Yamahara et al, 2015;Jin et al, 2019). Previous studies have shown that podocyte autophagy insufficiency is found in diabetic patients accompanied by massive proteinuria, and impaired podocyte autophagy exacerbated proteinuria in DN, these studies indicate the importance of podocyte autophagy in the pathogenesis of DN (Kume and Koya, 2015;Lenoir et al, 2015;Tagawa et al, 2016).…”
Section: Introductionmentioning
confidence: 86%
“…Autophagy is a highly conserved intracellular catabolic process for degradation of proteins and organelles via the lysosomal pathway (Mizushima and Komatsu, 2011;Mizushima et al, 2008). As terminally differentiated cells, podocytes exhibit a high level of basal autophagy, which play a pivotal role for maintaining podocyte's homeostasis (Hartleben et al, 2010;Yasuda-Yamahara et al, 2015;Jin et al, 2019). Previous studies have shown that podocyte autophagy insufficiency is found in diabetic patients accompanied by massive proteinuria, and impaired podocyte autophagy exacerbated proteinuria in DN, these studies indicate the importance of podocyte autophagy in the pathogenesis of DN (Kume and Koya, 2015;Lenoir et al, 2015;Tagawa et al, 2016).…”
Section: Introductionmentioning
confidence: 86%
“…HSP8A is one of the participants in the chaperonemediated autophagy (CAM) process, and studies have shown that CAM is involved in SLE and that adjustment of over-activated CAM is beneficial for SLE [26]. ULK1 was significantly higher in patients with lupus nephritis type IV and V-IV than in normal controls (p < 0.05), and its involvement in autophagy-related pathways influences the pathological process of lupus nephritis [27]. whereas the relationship between the other 5 autophagyrelated genes and SLE has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is a transcriptional regulator of autophagy, and inactive mTOR is a key signal for autophagosome biogenesis by activating the ULK kinase complex that occurs in conjunction with the PIK3C3-BECN1-ATG14 complex [ 17 ]. Autophagy is the lysosome-dependent pathway for protein degradation and is impaired in response to metabolic stresses such as autoimmune disease, certain kidney diseases, cancer, and neurodegeneration [ 30 ]. A recent study showed that Treg cells in SLE patients exhibited increased mTOR pathway activities, whereas autophagy and the suppressor function of Treg cells were diminished [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al showed deficient autophagy, which was evident by LC3-II and p62 expression and the number of autophagosomes in the MPC5 cells cultured with the IgAN supernatant, along with the upregulated expression of cleaved caspase-3 and a higher apoptosis rate [ 34 ]. However, Jin et al reported that the autophagy activity and expression pattern of autophagy-related markers in podocytes are significantly positively correlated with patients with LN types III, IV, and V–IV but negatively correlated with types II and V [ 30 ]. In the current study, there was a relatively high level of C3/IgG deposits in the glomeruli, and further research showed that podocyte injury occurs in the lupus group, and ADSC/miR-20a-ADSC treatment prevents podocyte damage.…”
Section: Discussionmentioning
confidence: 99%